Vetus melius est. Allegations of Novelty and Apology of Tradition in the Sixteenth-Century Quarrels between Humanists and Scholastics - Nowakowski, Dawid (Starość i młodość w literaturze i kulturze, 2016)
The paper presents the 16th-century dispute between scholastics and humanists over the proper shapeof intellectual tradition. Each side, using the motto “vetus melius est”, accused the other of inexcusableinnovation. The first group reveals strong unwillingness to any change and fed conviction that only maintainingof status quo will secure the Christianity. The second pointed to the poor memory of scholastics,who forgot the real ancient culture, and proclaimed that the change is not an innovation, but a restoration.In the end of the paper the author suggests an existence of possible relation between the humanistattitude toward tradition and the emergence of modern idea of progress.